2013
DOI: 10.1093/hmg/ddt222
|View full text |Cite
|
Sign up to set email alerts
|

ALS-associated mutations in FUS disrupt the axonal distribution and function of SMN

Abstract: Mutations in the RNA binding protein fused in sarcoma/translated in liposarcoma (FUS/TLS) cause amyotrophic lateral sclerosis (ALS). Although ALS-linked mutations in FUS often lead to a cytosolic mislocalization of the protein, the pathogenic mechanisms underlying these mutations remain poorly understood. To gain insight into these mechanisms, we examined the biochemical, cell biological and functional properties of mutant FUS in neurons. Expression of different FUS mutants (R521C, R521H, P525L) in neurons cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 77 publications
9
140
1
Order By: Relevance
“…In addition, FUS mutants were shown to redistribute SMN towards cytosolic FUS aggregates, eventually decreasing available levels of axonal SMN. Overexpression of SMN rescued the axonal defects induced by mutant FUS, suggesting that FUS mutations cause axonal defects, in part, through SMN sequestration [395]. Furthermore, FUS mutants, but not wild-type FUS, assembled into perinuclear stress granules in response to oxidative stress or heat-shock indicating that they may influence SG dynamics [396].…”
Section: Late-onset Neurodegenerationmentioning
confidence: 99%
“…In addition, FUS mutants were shown to redistribute SMN towards cytosolic FUS aggregates, eventually decreasing available levels of axonal SMN. Overexpression of SMN rescued the axonal defects induced by mutant FUS, suggesting that FUS mutations cause axonal defects, in part, through SMN sequestration [395]. Furthermore, FUS mutants, but not wild-type FUS, assembled into perinuclear stress granules in response to oxidative stress or heat-shock indicating that they may influence SG dynamics [396].…”
Section: Late-onset Neurodegenerationmentioning
confidence: 99%
“…FUS is involved in many cellular processes such as transcriptional regulation, RNA splicing, DNA repair, genomic integrity, and responses to DNA damage5. In polarized neurons, FUS has been shown to regulate spine formation and maintenance of spine stability, transport of mRNA (such as actin-regulating mRNA) in dendrites, axonal transport of survival motor neuron (SMN) protein, regulation of stability of GluA1 (a subunit of AMPA subtype of ligand-gated glutamate receptors) mRNA, and activity-dependent synaptic homeostasis, all suggesting an important role in synaptic formation and function6789.…”
mentioning
confidence: 99%
“…Synapses and distal axonal compartments are frequently involved in the early stages of ALS [6]. Mutations in FUS induce a redistribution of SMN from the axon to cytosolic FUS accumulations, which disrupt the function of SMN, thus leading to axonal defects [3]. Moreover, a study of 600 sporadic ALS patients found that an abnormal number of SMN1 copies (one or three rather than two) occurred more frequently in cases than controls (OR = 2.8, 95% CI: 1.8-4.4) [8].…”
Section: Discussionmentioning
confidence: 99%